Cross-conjugation increases the conductance of meta-connected fluorenones. Issue 29 (12th July 2019) - Alanazy, Asma; Leary, Edmund; Kobatake, Takayuki; Sangtarash, Sara; González, M. Teresa; Jiang, Hua-Wei; Bollinger, Gabino Rubio; Agräit, Nicolás; Sadeghi, Hatef; Grace, Iain; Higgins, Simon J.; Anderson, Harry L.; et al.
Abstract : In meta -connected fluorenones, the carbonyl group almost negates the effects of destructive quantum interference, compared with corresponding meta -connected fluorenes. Abstract : Charge transport is strongly suppressed by destructive quantum interference (DQI) in meta -connected 1, 1′-biphenyl-containing molecules, resulting in low electrical conductance. Surprisingly, we have found that DQI is almost entirely overcome by adding a bridging carbonyl, to yield a cross-conjugated fluorenone. This contrasts with other π-systems, such as para -connected anthraquinone, where cross-conjugation results in low conductance.